Pengaruh Employee Engagement, Teamwork, dan Burnout terhadap Kinerja Karyawan pada Bank Mandiri TASPEN: Kantor Cabang Pembantu Manna - Amanda, Juliya Septi; Markoni, Markoni; Fauzan, Fauzan (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the magnitude of the influence of Employee Angagement, TeamWork and Burnout on Employee Performance at Bank Mandiri Taspen (Manna Sub-Branch Office). The nature of this research is exploratori. Exploratory research is a research approach that aims to find information about a topic/problem that is not fully understood by a researcher. Researchers only prepare a number of questions as a guide to obtain primary data in the form of information, information, as the initial data needed. In this study the authors used the census sampling technique, namely the saturated sampling technique is a sampling technique when all members of the population are used as samples. Therefore, the author chose a sample using a saturated sampling technique because the population was relatively small. So that the sample used in this study amounted to 30 people. Based on the results There is an effect of employee engagement (X1) on employee performance (Y) of Bank Mandiri Taspen Company (Manna Sub-Branch Office) with a tsig value < α (0.001 < 0.05) and a tcount> ttable value (2.571> 1.69726) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X1 affects employee performance (Y). There is an effect of teamwork (X2) on employee performance (Y) of Bank Mandiri Taspen Company (Manna Sub-Branch Office) with a tsig value < α (0.004 < 0.05) and a tcount> ttable value (2.571> 1.69726) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X2 has an effect on employee performance (Y). There is an effect of burnout (X3) on employee performance (Y) of Bank Mandiri Taspen Company (Manna Sub-Branch Office) with a tsig value < α (0.003 < 0.05) and a tcount> ttable (2.571> 1.69726) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X3 has an effect on employee performance (Y).